Children's literature and Racial Relations: study on research with children (Olhar de Professor, 2025)
The aim of the present reflection is to analyze the use of children's literature as methodological instrument in research conducted with children, mainly in studies concerning children and racial relationships. A qualitative, bibliographical study was carried out based on BDTD/ibict theses and dissertations’ analysis. The adopted framework regards the Sociology of Childhood and Racial Relationships fields. It was possible observing how important it is to conduct studies aimed at reaching children, listening to them and taking into consideration their perspectives and emotions related to the ‘ethnic-racial relationships’ topic based on the analyzed research, which focused studies carried out with children and children's literature as mediating instrument for performed workshops and interventions.
Keywords: Children´s Literature; Racial Relations; Research with Children